Assessment of Ovarian Cancer Conditions From Exhaled Breath. Issue 2 (February 2015) - Amal, Haitham; Shi, Da-You; Ionescu, Radu; Zhang, Wei; Hua, Qing-Ling; Pan, Yue-Yin; Tao, Li; Liu, Hu; Haick, Hossam
Abstract : ABSTRACT: Most patients with ovarian cancer (OC) are diagnosed with advanced disease stages (III to IV) and have a 5-year survival rate less than 30%. Detecting OC in its early stages before it has metastasized could increase the 5-year survival rate to 85% to 90%. Previous studies have investigated a novel approach for the detection of OC based on measuring volatile organic compounds (VOCs) in exhaled breath; these disease-specific compounds evaporate from cancer cells and enter the surrounding environment. Using this principle, trained dogs showed an ability to distinguish OC tissues or blood samples from equivalent controls with almost 100% sensitivity and specificity. Because canine OC detection is not practical for widespread clinical use, scientists developed suitably sensitive analytical instrumentation for rapid detection of OC with similar accuracy as found with dogs. This pilot study examined the possibility that exhaled breath samples can noninvasively detect and discriminate women with OC from women that have no tumor(s) and from women that have benign genital tract neoplasia. The study population was composed of 3 groups: women with OC (n = 48), tumor-free control subjects (n = 48), and women with benign genetic tract neoplasia (n = 86). Gas chromatography linked with mass spectrometry was used to determine the chemical composition of the VOCs in the breath samples. Elevated concentrations of 5 compounds (decanal, nonanal, styrene, 2-butanone, and hexadecane) were found in the VOC samples from patients with cancer compared with the cancer-free volunteers. Analysis of the same samples with tailor-made nanoarrays showed good discrimination between women with OC and women who had either no tumor or benign genital tract neoplasia (71% for accuracy, sensitivity, and specificity). Conversely, nanoarray analysis was able to distinguish between the OC patients and the tumor-free control subjects (79% sensitivity, 100% specificity, and 89% accuracy). These preliminary findings show that a negative result with nanorray analysis could identify tumor-free women and avoid unnecessary complicated or expensive tests for OC in these patients. In patients with a positive result, the test will indicate the presence of OC with high probability. Further studies are needed with larger and more diverse populations to confirm and improve these promising results.